Composting of green waste - Syarini, binti Sajali (Faculty of Resource Science and Technology, 2007)
In this study, the compositing process using turned windrow system was carried out on organic waste namely green waste (includes all grass cutting and garden trimmings), which was obtained from the beautification of Kuching city collected by DBKU collection team. The objective was to evaluate the overall compost quality in relation to physical, chemical and biological attributes of the compost.